HUBUNGAN POWER OTOT LENGAN DAN BAHU DENGAN HASIL LEMPAR CAKRAM PADA SISWA PUTRA KELAS IX SMP NEGERI 27 PEKANBARU - Nurhidaya ningsi; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract :based on observation of writer on the student’s class nine of middle school’s 27 pekanbaru found the symptoms in a disk is still not good or less max. Research is aimed to knowing a significant connection to the power arm muscles and shoulders with the results in the disk on the student’s class IX of middle school’s 27 pekanbaru, which amounted 47 people. The technique sampling, sample the study was the son of middle school’s 27 pekanbaru, wihch has 47 people. The instrument of this test using the two hand medicine ball. The data in most analyzed using a technique the correlation of the moment. Based on the results of research and data processing in the statistics, then to conclude that for the relationship between variables X with variables Y in most value the. value r = -0 ,287 then rxy < rtabel that is (-0,287 < 0,291), in then Ha denied with other words there is not a significant connection between power arm muscles in this about the student’s class IX of the american junior district 27 pekanbaruKey word : Our arm muscles and shoulders to throw the disc.